2015
DOI: 10.1371/journal.pgen.1005467
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Driving ALK Fusion Genes and Genomic Landscape of Medullary Thyroid Cancer

Abstract: The genetic landscape of medullary thyroid cancer (MTC) is not yet fully understood, although some oncogenic mutations have been identified. To explore genetic profiles of MTCs, formalin-fixed, paraffin-embedded tumor tissues from MTC patients were assayed on the Ion AmpliSeq Cancer Panel v2. Eighty-four sporadic MTC samples and 36 paired normal thyroid tissues were successfully sequenced. We discovered 101 hotspot mutations in 18 genes in the 84 MTC tissue samples. The most common mutation was in the ret prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
67
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 34 publications
0
67
0
3
Order By: Relevance
“…So far, only a few non-RET molecular alterations have been detected in MTC, including primarily HRAS and KRAS mutations, as well as BRAF mutations (0-7%) (Moura et al 2015). In a recent study, also very few mutations in genes encoding KIT, MLH1, STK11, and MET were reported (Ji et al 2015). In addition, ALK rearrangements were found in 2 of 98 screened cases (Ji et al 2015).…”
Section: :6mentioning
confidence: 94%
See 1 more Smart Citation
“…So far, only a few non-RET molecular alterations have been detected in MTC, including primarily HRAS and KRAS mutations, as well as BRAF mutations (0-7%) (Moura et al 2015). In a recent study, also very few mutations in genes encoding KIT, MLH1, STK11, and MET were reported (Ji et al 2015). In addition, ALK rearrangements were found in 2 of 98 screened cases (Ji et al 2015).…”
Section: :6mentioning
confidence: 94%
“…In a recent study, also very few mutations in genes encoding KIT, MLH1, STK11, and MET were reported (Ji et al 2015). In addition, ALK rearrangements were found in 2 of 98 screened cases (Ji et al 2015). RAS mutations seem to be mutually exclusive with RET mutations and have been reported in different series to be present in approximately 0-81.3% of RET wild-type sporadic MTC (Moura et al 2015).…”
Section: :6mentioning
confidence: 97%
“…In addition, RAS and RET are mutually exclusive in MTC cases. A few anecdotal MTC cases harboring a RET or ALK rearrangement have been very recently described (Grubbs et al 2015, Ji et al 2015.…”
Section: :4mentioning
confidence: 99%
“…Despite the many genetic alterations that have been described for thyroid cancer and the most recent efforts to find other activated oncogenes, approximately 5-10% of PTCs, 50-60% of MTCs, and 10% of ATCs and PDTCs are still negative for all known genetic abnormalities (Soares et al 2011, Giordano et al 2014, Ji et al 2015.…”
Section: :4mentioning
confidence: 99%
“…Although very rare, kinesin family member 5B (KIF5B), kinesin light chain 1 (KLC1), TFG, striatin (STRN), protein tyrosine phosphatase, non-receptor type 3 (PTPN3), Huntingtin interacting protein (HIP1), translocated promoter region protein (TPR), SEC31A, SQSTM1, DCTN1, and cysteine-rich transmembrane BMP regulator 1 (CRIM1) have also been reported to function as an ALK fusion partner in NSCLC. [100][101][102][103][104][105][106][107][108][109] After the discovery of EML4-ALK in NSCLC, ALK fusions were explored and identified in different epithelial tumors, including renal cancer, [110][111][112][113] 116 The frequencies of these fusions are 1-2% in thyroid cancer [120][121][122][123] and less than 1% in kidney and colon cancers. 112,118 Recent studies have revealed that approximately 10% of Spitz tumors harbor ALK fusions.…”
mentioning
confidence: 99%